Research on Risk Factors Affecting High-Speed Railway Delays in China Based on Association Rules - WANG, Aidi; XING, Yingying; LANG, Hong; WANG, Hongwei; LU, Jian John (Promet - Traffic&Transportation, 2026)
This study aimed to investigate the contributing factors to high-speed railway (HSR) delays and their interdependency in China. A total of 420 records of high-speed railway delays in China were collected, and 15 risk factors related to high-speed railway delays were extracted. Descriptive statistics were used to illustrate the causes of HSR delays in terms of device, personnel and environmental conditions. The association rule mining technique was further applied to explore contributing factors that cause HSR delays, revealing the underlying mechanisms of delay occurrence. The results show that HSR delays of more than 1 hour are most likely caused by foreign objects hanging on the catenary. Moreover, 65% of HSR delays are within the range of 9–30 minutes. Among delay events with durations of 9 to 30 minutes, about 9% of are caused by the fault of on-board train control equipment, mainly the Automatic Train Protection (ATP). Regarding short delays of HSR within 8 minutes, the most likely cause is platform screen door faults, followed by traveller’s misconduct and train door faults. This study offers transportation agencies insights into HSR delay causes and aids in developing policies and engineering measures to reduce delays.